2014
DOI: 10.3389/fonc.2014.00079
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activity of Heparan Sulfate Biosynthetic Machinery is Specifically Impaired in Benign Prostate Hyperplasia and Prostate Cancer

Abstract: Heparan sulfates (HSs) are key components of mammalian cells surface and extracellular matrix. Structure and composition of HS, generated by HS-biosynthetic system through non-template-driven process, are significantly altered in cancer tissues. The aim of this study was to investigate the involvement of HS-metabolic machinery in prostate carcinogenesis. Transcriptional patterns of HS-metabolic enzymes (EXT1, EXT2, NDST1, NDST2, GLCE, 3OST1/HS3ST1, SULF1, SULF2, HPSE) were determined in normal, benign, and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
4
19
1
Order By: Relevance
“…It was shown that the expression levels of exostosin proteins EXT1 and EXT2 oppositely affect the amount of glucosaminyl N-deacetylase/N-sulfotransferase NDST1 in the cell, which, in turn, greatly influences HS structure; 39 knock-out of sulfatase genes (Sulf) dynamically modulates the expression of the Hs2st and Hs6st heparan sulfate sulfotransferase genes resulting to the changes in HS sulfation and significant effects on fibroblast growth factor signaling; 40 ectopic over-expression of D-glucuronyl C5-epimerase (GLCE) results in proportional up-regulation of expression of key genes and total transcriptional activation of HS-biosynthetic machinery in prostate cancer cells. 33 The presented results support an existence of the self-regulating mechanism for the coordinated transcription of HS metabolism-involved genes. As to cancer-related changes of the HS biosynthetic machinery, the obtained data show tissue-specific changes in total expression level and transcriptional pattern of the system in different tumors.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…It was shown that the expression levels of exostosin proteins EXT1 and EXT2 oppositely affect the amount of glucosaminyl N-deacetylase/N-sulfotransferase NDST1 in the cell, which, in turn, greatly influences HS structure; 39 knock-out of sulfatase genes (Sulf) dynamically modulates the expression of the Hs2st and Hs6st heparan sulfate sulfotransferase genes resulting to the changes in HS sulfation and significant effects on fibroblast growth factor signaling; 40 ectopic over-expression of D-glucuronyl C5-epimerase (GLCE) results in proportional up-regulation of expression of key genes and total transcriptional activation of HS-biosynthetic machinery in prostate cancer cells. 33 The presented results support an existence of the self-regulating mechanism for the coordinated transcription of HS metabolism-involved genes. As to cancer-related changes of the HS biosynthetic machinery, the obtained data show tissue-specific changes in total expression level and transcriptional pattern of the system in different tumors.…”
Section: Discussionsupporting
confidence: 71%
“…38 An interesting aspect of the results is that the balance between key genes was maintained in all normal tissues, in spite of 1,5-fold difference in total transcriptional activities, supporting an existence of molecular mechanism tightly coordinating the expression of the HS biosynthesis-involved genes. 33 The mechanism seems include feedback loop, where any gene is able to appropriately coordinate an expression of other gene(s). It was shown that the expression levels of exostosin proteins EXT1 and EXT2 oppositely affect the amount of glucosaminyl N-deacetylase/N-sulfotransferase NDST1 in the cell, which, in turn, greatly influences HS structure; 39 knock-out of sulfatase genes (Sulf) dynamically modulates the expression of the Hs2st and Hs6st heparan sulfate sulfotransferase genes resulting to the changes in HS sulfation and significant effects on fibroblast growth factor signaling; 40 ectopic over-expression of D-glucuronyl C5-epimerase (GLCE) results in proportional up-regulation of expression of key genes and total transcriptional activation of HS-biosynthetic machinery in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 EXT1 expression was significantly lower in benign prostatic hyperplasia (BPH) and PCa in comparison with normal prostate tissue. 35 IRX5 has been linked to human PCa through downregulation via vitamin D3 [1,25(OH)2D3] in LNCaP cells; VitD3 is a potent inhibitor of the proliferation of many different cancer cell types. Knockdown of IRX5 resulted in an increase in p21 protein expression, G2-M arrest, and apoptosis, partially mediated by p53.…”
Section: Discussionmentioning
confidence: 99%